Enjoy Poverty, Please: Renzo Martens brug af et dobbelt publikum - Kristensen, Jeppe (Peripeti, 2012)
The media play an important part in modern art that has to cope with a world ever more functionally differentiated while displaying its furthest parts ever more explicit through the media. This article analyzes Renzo Martens’ use of a double audience in the piece Enjoy Poverty, aiming to show how very specific audience relations can play a part in incorporating the schism between closeness and distance. Through Niklas Luhmann’s systems theoretical considerations on the art system it is shown how Martens by chalking journalistic documentary in his performed interactions gives form to the schism by on one hand harshly criticizing aid- and media systems unable to observe their surroundings in a proper manner, and on the other hand being formed as a piece solely interested in being art.